A Single Dose of Indomethacin Does Not Prolong Premotor Reaction Time in Young, Healthy Adults: A Randomized, Placebo-Controlled, Double-Blind, Cross-Over Study - Özden ÖZYEMİŞCİ TAŞKIRAN and Aslı GENCAY CAN and Zafer GÜNENDİ and Mehmet BEYAZOVA (Archives of Rheumatology, 2012)
Objectives: In this study, we aimed to investigate the hypothesis that a single dose of indomethacin may affect information processing speed in healthy subjects. Patients and methods: In this cross-sectional, randomized, placebo controlled, double-blind, cross-over study, 30 healthy adults (8 males, 22 females; mean age 32.4±5.3 years; range 24 to 42 years) received a single dose of 25 mg indomethacin (Endol, oral capsule, DEVA Pharmaceutics, Kartepe, Turkey) and placebo. Premotor reaction and response times were measured electromyographically before and after the administration of preparations by a blinded researcher in the Electrophysiology Laboratory at Gazi University, Faculty of Medicine, Department of Physical Medicine and Rehabilitation, Ankara. Results: Premotor reaction time measurements before and after a single dose of indomethacin were 169.1±36.3 and 160.2±29.5 msec, respectively (p=0.113). Premotor reaction time measurements before and after a single dose of placebo were 158.7±35.5 and 161.5±36.3 msec, respectively (p=0.516). There was also no statistically significant difference between premotor reaction time measurements of the indomethacin and placebo groups. Conclusion: A single dose of indomethacin did not change premotor reaction time and response time in healthy adults. This may suggest that indomethacin has no effect on the information processing speed in healthy adults.